Parsley production using organic fertilizers before planting and in top dressing - Luís, Débora Cristina Mastroleo; Cardoso , Antonio Ismael Inácio; Nepomuceno Alves, Thatiane; Pelvine, Raíra Andrade; Oliveira, Marcelo Munhoz Venâncio de (Comunicata Scientiae, 2023)
The objective of this research was to evaluate the effect of two organic fertilizers used before planting and in top dressing in the production of parsley. Seven treatments were evaluated, resulted from the factorial 2 x 3 + 1: two organic fertilizers (castor bean cake, and hoof and horn powder) x 3 modes of application (100% before planting; 100% in top dressing; 50% before planting and 50% in top dressing) + 1 control. The experimental design was in randomized blocks, with five replications and plots of 1 m2. Two harvests were done and in both the following characteristics were evaluated: the relative chlorophyll index ("Spad’’), plant height, fresh (FW) and dry (DW) matter weight of shoot and macronutrients accumulation. There was no significant difference for the ‘’Spad” index in both harvests. For the other characteristics, the control was inferior to the other treatments. In the comparison among application modes, the treatment with castor bean cake, 100% before planting, was inferior to the other applications modes of this fertilizer for FW and DW. For hoof and horn powder, the 100% in top dressing application mode was superior to other applications. In the comparison between fertilizers, the hoof and horn powder was superior to castor bean cake in both harvests when application was done 100% before planting. The descending order of macronutrients accumulation was: K > N > Ca > P > Mg. Therefore, it is recommended to apply hoof and horn powder, 100% in top dressing application.